Asas pembenihan patin hitam - Yusof, Muhammad Fitri (2021)
This is a note about methods used for breeding Sutchi Catfish (Pangasianobon hypophthalmus) locally known as Patin Hitam. It includes pond preparation, broodstock preparation, broodstock selection, breeding preparation, hormone induction, egg stripping, fertilization, and egg incubation.